Autoregulation of ZEB2 expression for zearalenone production in Fusarium graminearum. Issue 5 (25th June 2015) - Park, Ae Ran; Son, Hokyoung; Min, Kyunghun; Park, Jinseo; Goo, Jae Hwan; Rhee, Sangkee; Chae, Suhn‐Kee; Lee, Yin‐Won
Summary Several Fusarium species produce the polyketide mycotoxin zearalenone (ZEA), a causative agent of hyperestrogenic syndrome in animals that is often found in F. graminearum–infected cereals in temperate regions. The ZEA biosynthetic cluster genes PKS4, PKS13, ZEB1 and ZEB2 encode a reducing polyketide synthase, a non‐reducing polyketide synthase, an isoamyl alcohol oxidase and a transcription factor respectively. In this study, the production of two isoforms (ZEB2L and ZEB2S) from the ZEB2 gene in F. graminearum via an alternative promoter was characterized. ZEB2L contains a basic leucine zipper (bZIP) DNA‐binding domain at the N‐terminus, whereas ZEB2S is an N‐terminally truncated form of ZEB2L that lacks the bZIP domain. Interestingly, ZEA triggers the induction of both ZEB2L and ZEB2S transcription. ZEB2L and ZEB2S interact with each other to form a heterodimer that regulates ZEA production by reducing the binding affinity of ZEB2L for the ZEB2L gene promoter. Our study provides insight into the autoregulation of ZEB2 expression by alternative promoter usage and a feedback loop during ZEA production; this regulatory mechanism is similar to that observed in higher eukaryotes.